Formulation of orodispersible atenolol-β-cyclodextrin tablets with co-processed crospovidone-croscarmellose sodium and poloxamer 188 - Karina Citra Rani; Nani Parfati; Linda Yosanti; I Gusti Ayu Yulivia Rosa Indah (Universitas Ahmad Dahlan, 2019)
The use of conventional tablets in geriatric patients is currently limited because of a decrease in their physiological functions, such as tremor and difficulty of swallowing pills, which lowers their compliance with drug therapy. Hypertension, one of the degenerative diseases suffered by geriatric patients, is treatable with atenolol tablets or capsules that are less soluble in water or, in other words, has a poor dissolution. This research attempted to improve the dissolution of atenolol by formulating it into orodispersible tablets (ODTs), and as such, the disintegration time was modified by adding co-processed crospovidone-croscarmellose sodium in 1:1 ratio. Moreover, Poloxamer® 188 was added to the formulation of atenolol-β-cyclodextrin inclusion complex. The post-compression test revealed that ODTs disintegrated quickly within 36.67±1.21 seconds (<60 seconds) and had physical characteristics that met the pharmaceutical requirements. The amount of atenolol dissolved within 30 minutes in the dissolution study was 84.39% (%Q30 minutes). The results of the accelerated stability study (at 40 °C and RH 75±5 %) for two weeks proved that the physical and chemical characteristics of the produced orodispersible atenolol tablets were stable.